Influence of prostaglandin analogues on intraocular pressure fluctuations in body position change ABSTRACT - A.A. Antonov; S.V. Vostrukhin; A.V. Volzhanin; A.A. Vitkov; A.M. Akimov; I.I. Asinovskova (РМЖ "Клиническая офтальмология")
A.A. Antonov1, S.V. Vostrukhin2, A.V. Volzhanin1, A.A. Vitkov1, A.M. Akimov3, I.I. Asinovskova4 1 Scientific Research Institute of Eye Diseases, Moscow, Russian Federation 2JSC MedSef Ramenskoe, Ramenskoe, Russian Federation 3 I.M. Sechenov First Moscow State Medical University (Sechenov University),   Moscow, Russian Federation 4A.I. Yevdokimov Moscow State University of Medicine and Dentistry, Moscow,  Russian Federation Aim: to assess the effects of prostaglandin F2α analogues on intraocular pressure (IOP) fluctuations when changing body position. Patients and Methods: thirty-eight patients (50 eyes) with newly diagnosed primary open-angle glaucoma (POAG). Patients were examined before and one month after prescribing travoprost, a prostaglandin F2α analogue. During the examination, IOP was measured by Icare pro rebound tonometry and applanation tonometry (corneal-compensated IOP/ccIOP and Goldmann-correlated IOP/IOPg) in a sitting position. Next, IOP was measured by Icare tonometer twice with a 5-min interval in a supine position. Finally, IOP was measured by Icare tonometry and applanation tonometry (IOPcc, IOPg) in the sitting position. Results: baseline IOPcc, IOPg, and IOP measured by Icare were 25.4±3.2 mm Hg, 25.7±2.3 mm Hg, and 22.9±3.4 mm Hg, respectively. IOP levels (Icare tonometry) in the supine position were 23.7±3.3 mm Hg and 24.0±3.3 mm Hg, respectively. In repeated measurements in the sitting position, IOPcc, IOPg, and IOP measured by Icare were 25.4±3.2 mm Hg, 25.7±2.4 mm Hg, and 22.3±3.4 mm Hg. One month after starting treatment with travoprost, IOPcc, IOPg, and IOP measured by Icare reduced to 18.2±2.7 mm Hg, 18.2±1.8 mm Hg, and 16.6±2.5 mm Hg, respectively. IOP levels (Icare tonometry) in the supine position were 17.3±2.8 mm Hg and 17.2±2.7 mm Hg, respectively. In repeated measurements in the sitting position, IOPcc, IOPg, and IOP measured by Icare were 18.0±2.3 mm Hg, 18.4±1.8 mm Hg, and 16.2±2.5 mm Hg, respectively. When transiting in a supine position, the differences in IOP levels were 0.83±1.04 mm Hg at baseline and 0.77±1.41 mm Hg after one month. When transiting in a sitting position, the differences in IOP levels were 1.66±1.24 mm Hg at baseline and 0.99±0. 98 mm Hg after one month. Conclusion: travoprost as a starting monotherapy for POAG provides a long-lasting IOP reduction and minimizes its fluctuations when changing body position Keywords: glaucoma, intraocular pressure, body position, rebound tonometry, prostaglandin analogue, travoprost. For citation: Antonov A.A., Vostrukhin S.V., Volzhanin A.V. et al. Influence of prostaglandin analogues on intraocular pressure fluctuations in body position change. Russian Journal of Clinical Ophthalmology. 2022;22(2):103–107 (in Russ.). DOI: 10.32364/2311-7729-2022-22-2-103-107.